2022
DOI: 10.1186/s12902-022-01259-1
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal sleep duration and bone mineral density: a cross-sectional study of the National Health and Nutrition Examination Survey (NHANES) 2007–2014

Abstract: Background This study aimed to investigate the association between sleep duration and bone mineral density (BMD) and determine whether vitamin D (VD) status influenced the association between sleep duration and BMD. Methods National Health and Nutrition Examination Survey 2007–2014 participants aged ≥ 40 years were included in this study. BMD testing was conducted with dual-energy X-ray absorptiometry examinations. Moreover, all individuals were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition, short sleep was related to an increased fracture risk (Cauley et al, 2019), and both, short and long sleep (≤ 5 or ≥ 10 h) were accompanied by an increased risk of falls (Cauley et al, 2019). Long sleep duration (> 8 h) was further reported to be related to reduced bone mineral density among nearly 4400 National Health and Nutrition Examination Survey (NHANES) participants (Tang et al, 2022). In another study, Lucassen et al (2017) found that lower sleep quality and late sleep onset, as assessed by the PSQI, present risk factors for osteopenia and sarcopenia in middle‐aged (aged 45–65 years) men and women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, short sleep was related to an increased fracture risk (Cauley et al, 2019), and both, short and long sleep (≤ 5 or ≥ 10 h) were accompanied by an increased risk of falls (Cauley et al, 2019). Long sleep duration (> 8 h) was further reported to be related to reduced bone mineral density among nearly 4400 National Health and Nutrition Examination Survey (NHANES) participants (Tang et al, 2022). In another study, Lucassen et al (2017) found that lower sleep quality and late sleep onset, as assessed by the PSQI, present risk factors for osteopenia and sarcopenia in middle‐aged (aged 45–65 years) men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Previously and in contrast to our results, relationships of sleep characteristics with bone mineral density, ultrasound‐based parameters, or fractures have been documented (Bevilacqua et al, 2020; Cauley et al, 2019; Chen et al, 2014; Fu et al, 2011; Lucassen et al, 2017; Ochs‐Balcom et al, 2020; Sasaki et al, 2016; Sforza et al, 2013; Specker et al, 2007; Swanson et al, 2021; Tang et al, 2022; Terzi & Yilmaz, 2016). Yet, most previous studies (Bevilacqua et al, 2020; Cauley et al, 2019; Chen et al, 2014; Fu et al, 2011; Lucassen et al, 2017; Ochs‐Balcom et al, 2020; Sasaki et al, 2016; Sforza et al, 2013; Specker et al, 2007; Swanson et al, 2021; Tang et al, 2022; Terzi & Yilmaz, 2016) assessed sleep characteristics solely by self‐reports using standardised or study‐specific questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of VD3 deficiency with sleep among older adults has also been explored. Plenty of literature has found that low levels of VD3 are related to short or long sleep durations, decreased sleep efficiency, and sleep fragmentation [38][39][40][41][42][43][44]. For instance, based on 207 women aged 55 years or older in Macao, China, one study found that both short and long sleep durations were significantly associated with VD3 deficiency [40].…”
Section: Introductionmentioning
confidence: 99%